Pola Layanan Bimbingan Konseling dalam Mendukung Motivasi dan Perkembangan Siswa - Silvi Aprilliani; Syaila Putri Maharani; Maryam Maryam; Ratih Juniarti Rahayu; Naufelya Panca Pradana; Zakiyah Nurfatihah; Nasrul Hidayat Permana; Priya Satria Partisara; Ari Firmansyah; Adhit Diana Hidayat; Feida Nurlaila Istiadah (CV. ITTC INDONESIA, 2026)
Guidance and Counseling (GC) services are an integral part of the school education system that play an important role inSupporting students’ learning motivation and optimal development. The implementation of GC services requires a well-planned Service pattern that is adjusted to students’ needs and developmental stages. This study aims to describe the pattern of Guidance And Counseling services in supporting students’ motivation and development based on the Multi-Tiered System of Supports (MTSS) Approach. This research employed a qualitative method with a descriptive approach. The study was conducted at SMP Al-Muttaqin And SMP Negeri 2 Cisayong, with Guidance and Counseling teachers as the research subjects. Data were collected through Observation, interviews, and documentation analysis. The results indicate that GC service patterns are implemented progressively Through Tier 1 (universal services), Tier 2 (responsive services), and Tier 3 (intensive services), which contribute to improving Students’ learning motivation and supporting their personal, social, and academic development. The implementation of a Structured MTSS-based GC service pattern enables guidance services to be delivered more systematically and in accordance with Students’ needs within the school environment.